1991
DOI: 10.1093/ageing/20.6.430
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Levels in Hospitalized Elderly Patients: A Comparison with Community Based Volunteers

Abstract: Twenty-one-hour melatonin plasma profiles were studied in 15 normal elderly volunteers from the community, and eight who had been in hospital for more than six weeks and who had not been exposed to strong natural lighting. The hospital group had significantly higher daytime plasma melatonin levels, an earlier nocturnal rise, and the timing of their secretory profiles was more variable. These results suggest that currently used artificial and supplementary natural lighting may not be sufficient to suppress mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The reduced pain in the melatonin group (evidenced by lower pain scores) may be related to better sedation levels, which therefore promoted better quality of sleep. Also, previous studies have demonstrated that melatonin both induced sleep and improved sleep quality [3,25]. Naguib and Samarkandi [5] compared 5 mg oral melatonin and 15 mg midazolam for effects on sedation and found that midazolam produced higher sedation levels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The reduced pain in the melatonin group (evidenced by lower pain scores) may be related to better sedation levels, which therefore promoted better quality of sleep. Also, previous studies have demonstrated that melatonin both induced sleep and improved sleep quality [3,25]. Naguib and Samarkandi [5] compared 5 mg oral melatonin and 15 mg midazolam for effects on sedation and found that midazolam produced higher sedation levels.…”
Section: Discussionmentioning
confidence: 97%
“…Environmental changes such as hospital stay, medication, pain, stress, and general anesthesia can affect the sleepwake cycle. Plasma melatonin levels, which play an important role in the regulation of sleep-wake cycles, are decreased after surgery and in hospitalized patients [3]. Exogenous melatonin, which is often administered orally, has a number of beneficial effects such as facilitating the onset and the quality of sleep [4]; alleviating preoperative anxiety and producing sedation [5]; regulating circadian rhythms [6]; and producing anticonvulsant and antiinflammatory effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…Altered circadian patterns of melatonin or virtually nonexistent secretion have also been noted in ICU patients 77,78. This abnormality is associated with mood and sleep disorders that are observed in elderly hospitalized patients79 and may contribute to slower recovery in the critically ill 80. Melatonin supplementation may serve as a promising new way to manage sleep disruption and delirium in the ICU; however, the research in this area is sparse 81.…”
Section: Sleep In the Icumentioning
confidence: 99%
“…The circadian rhythm does not only influence sleep wake patterns, but also dictates physiological and cellular functions that allows for adaption to cyclic environmental changes 40 . Evidence suggests the relationship between circadian function and disease is quite complex and multidirectional 15,16,26,32,[40][41][42][43] . There is loss of normal diurnal variation in melatonin secretion in critically ill patients 43 , likely contributing to circadian misalignment.…”
Section: Effects Of Swd In Hospitalized Patientsmentioning
confidence: 99%